Development of synthetic open porous structures for improved heat transfer. (October 2020) - August, Anastasia; Jamshidi, Farshid; Kneer, Aron; Wolf, Rainer H.; Wirtz, Michael; Nestler, Britta
Highlights: Water pipes, heated from the outside, are lined with an open porous inner structure. The heat can quickly reach the water via the large contact surface. But also the flow resistance increases. We search for digital models for line pipe elements and qualify them computationally. For better comparability, the samples have almost the same surface area and porosity. Abstract: If water pipes, which are heated from the outside, are lined with an open porous inner structure, the heat can quickly reach the water via the large contact surface. At the same time, the flow resistance increases due to the presence of the interior. We aim for computationally designing an internal structure that is advantageous for both heat transfer and flow. In this paper we present our path from digital models to metallic pipe components with specifically adjusted properties: First, we design digital models for line pipe elements and qualify them with the help of computer simulations. As a next step, the algorithmically generated samples are printed in 3D. The 3D-printed polylactide models serve as prototypes for the production of metallic pipes, which are then tested in experiments. In this work, three types of inner structures are evaluated: Metal foam, cuboid fins and curved fins. For better comparability, we provide them with almost the same specific surface area and porosity. The use of open-pore metal foams is advantageous for greater heat transfer and fins enable smaller pressure drop.